Exogenous Application of Defence Signalling Compounds Stimulate Natural Defence Responses against Alternaria Blight and Seed Quality in Radish - Rohiwala, P.; Bharat, N. K.; Bhardwaj, R.; Gupta, B. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted in the Department of Seed Science and Technology, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during 2017–2019 to test the efficacy of plant defence signalling compounds to manage alternaria blight and improve seed quality of radish cv. Japanese white . The experiment was composed of 13 treatments which included three different concentrations of four plant defence activators viz., salicylic acid (50, 75 and 100 ppm), methyljasmonate (55, 110 and 165 ppm), β-aminobutyric acid (250, 500 and 750 ppm), potassium nitrate (1%, 1.5% and 2%) and untreated control. The treatments were applied in the form of foliar applications at three growth stages of the crop viz., initiation of flowering stalk, flowering and pod development. The results highlighted that lowest severity of alternaria blight i.e. 9.44% and11.31% was recorded from the plants sprayed with 750 ppm β-aminobutyric acid and 100ppm salicylic acid respectively. The maximum seed yield was observed with foliar application of 100ppm salicylic acid (379.71 g plot-1) followed by 2% potassium nitrate (352.72 g plot-1). The other parameters related to seed yield and quality such as number of silique plant-1, length of siliqua, number of seeds siliqua-1, 1000 seed weight, seed germination, speed of germination, SVI-I and SVI-II were observed significantly higher with the foliar application of salicylic acid at 100 ppm as compared to other treatments. The results indicated the potential use of salicylic acid at 100 ppm in radish seed crop for management of alternaria blight and production of good quality seeds.